Fire behaviour and smoke modelling: model improvement and measurement needs for next-generation smoke research and forecasting systems - Liu, Yongqiang; Kochanski, Adam; Baker, Kirk R.; Mell, William; Linn, Rodman; Paugam, Ronan; Mandel, Jan; Fournier, Aime; Jenkins, Mary Ann; Goodrick, Scott; Achtemeier, Gary; Zhao, Fengjun; et al. (International journal of wildland fire, 2019)
There is an urgent need for next-generation smoke research and forecasting (SRF) systems to meet the challenges of the growing air quality, health and safety concerns associated with wildland fire emissions. This review paper presents simulations and experiments of hypothetical prescribed burns with a suite of selected fire behaviour and smoke models and identifies major issues for model improvement and the most critical observational needs. The results are used to understand the new and improved capability required for the next-generation SRF systems and to support the design of the Fire and Smoke Model Evaluation Experiment (FASMEE) and other field campaigns. The next-generation SRF systems should have more coupling of fire, smoke and atmospheric processes. The development of the coupling capability requires comprehensive and spatially and temporally integrated measurements across the various disciplines to characterise flame and energy structure (e.g. individual cells, vertical heat profile and the height of well-mixing flaming gases), smoke structure (vertical distributions and multiple subplumes), ambient air processes (smoke eddy, entrainment and radiative effects of smoke aerosols) and fire emissions (for different fuel types and combustion conditions from flaming to residual smouldering), as well as night-time processes (smoke drainage and super-fog formation).